Hybrid Power System Design for Autonomous Ground Robots - Al-Tameemi, Ali Qahtan (2018)
A Master of Science thesis in Mechatronics Engineering by Ali Qahtan Al-Tameemi entitled, “Hybrid Power System Design for Autonomous Ground Robots”, submitted in November 2018. Thesis advisor is Dr. Shayok Mukhopadhyay. Soft and hard copy available.